Health Care Policy and Outcomes after Colon and Rectal Surgery: What Is the Bigger Picture?—Cost Containment, Incentivizing Value, Transparency, and Centers of Excellence - Bhama, Anuradha R.; Holubar, Stefan D.; Delaney, Conor P. (Clinics in Colon and Rectal Surgery, 2019)
Early in the 21st century, the costs of health care in the United States have spiraled out of control, where the per capita spending is $9,237 per person—the highest in the world. By 2020, an estimated 20% of GDP will be spent on health care. The issue of cost and quality is now becoming a national crisis, with ∼50% of hospitals losing money on clinical operations, forcing closure of essential critical access hospitals, and forcing health care workers to relocate or change professions. This crisis will only worsen with the graying of America, as an estimated 17% of Americans will be over the age of 65 years by the year 2020. The policy and financial structures on which these changes are based are important factors of which practicing surgeons should be aware. This review discusses recent national health care policy reform and specific topics including cost-containment legislation, value-based incentives and penalties, transparency, and centers of excellence in colorectal surgery.
Keywords: colectomy; proctectomy; health care policy; surgical outcomes; centers of excellence